2001
DOI: 10.1038/sj.onc.1204331
|View full text |Cite
|
Sign up to set email alerts
|

When the SWI/SNF complex remodels … the cell cycle

Abstract: Mammalian cells contain several chromatin-remodeling complexes associated with the Brm and Brg1 helicaselike proteins. These complexes likely represent the functional homologs of the SWI/SNF and RSC complexes found in Saccharomyces cerevisiae. The mammalian chromatin-remodeling complexes are involved in both activation and repression of a variety of genes. Several lines of evidence also indicate that they play a speci®c role in the regulation of cell growth. Brm is down-regulated by ras signaling and its force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 79 publications
11
145
1
1
Order By: Relevance
“…The BRM gene in BRG1/BRM-deficient cell lines is not mutated We and others have noted that BRG1 and BRM protein levels are consistently lost together in a variety of cancer cell lines (Muchardt and Yaniv, 2001;Reisman et al, 2002). BRG1 has been found to be mutated (Wong et al, 2000)) in these cell lines, but the various mechanisms that might underlie BRM loss have not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The BRM gene in BRG1/BRM-deficient cell lines is not mutated We and others have noted that BRG1 and BRM protein levels are consistently lost together in a variety of cancer cell lines (Muchardt and Yaniv, 2001;Reisman et al, 2002). BRG1 has been found to be mutated (Wong et al, 2000)) in these cell lines, but the various mechanisms that might underlie BRM loss have not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of BRM loss in primary cancers other than lung has not yet been determined, although loss of BRM in a variety of cancer cell lines has been reported (Muchardt and Yaniv, 2001;Reisman et al, 2003). We immunostained six different high-density, tissue-specific Figure 4 (a) MG2-13 cells were treated with butyrate for 72 h and then butyrate was removed.…”
Section: Brm Expression Is Lost In a Variety Of Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Its loss occurs in both familial and sporadic renal and extra-renal rhabdoid tumors, as well as in certain central nervous system tumors (Biegel et al, 2002;Biegel and Pollack, 2004;Bourdeaut et al, 2007); however, not more than 50 patients have been identified with this defect, and loss of BAF47 has very infrequently been observed in any adult tumor (Grand et al, 1999;Manda et al, 2000;Yuge et al, 2000;DeCristofaro et al, 2001). Instead, in adult tumors, the major cancer defect in SWI/SNF appears to be the loss of BRG1, BRM or both (Muchardt and Yaniv, 2001). This appears to occur between 10 and 20% of a variety of tumor types (Reisman et al, 2003;Glaros et al, 2007).…”
Section: The Swi/snf Complex Is Involved In Differentiationmentioning
confidence: 99%